KEANEKARAGAMAN DAN POLA DISTRIBUSI BIVALVIA DI TELUK PANGPANG BLOK JATI PAPAK TAMAN NASIONAL ALAS PURWO BANYUWANGI - Zahro, Lutfiatus; As’ari, Hasyim; Ardyansyah, Fuad; Dagsy, Irqami Rachma Dwi; Firmansyah, Moh. (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2024)
Alas Purwo National Park in Banyuwangi is one of the conservation areas of mangrove forest potential big enough one of them is the Teluk Pangpang Blok Jati Papak which is the intertidal area, a lot of marine life that live in the region one of which is the bivalves. This study aims to determine diversity and the distribution pattern of bivalves in the Teluk Pangpang Blok Jati Papak. This study was conducted in 25 Mei - June 1, 2016. Determination of the sampling method used in this research is purposive sampling. Sampling sites are divided into three stations, with the distance between stations is 500 m, in each station there are four transects on each transect contained 10 plot. set the distance between transects 15 m and the distance between the plots 5 m with a plot measuring 2 × 2m. Measurement parameters abiotic do is measure temperature, salinity and pH. The research found 8 species of bivalves that Anomalodiscus squamosus, Placamen chlorotica, Pitar citrus, Chamelea gillina, Mactra grandis, Hiatula chinensis, Tellina timorensis, Anadara granosa. An index value of diversity bivalves in the Teluk Pangpang Blok Jati Papak categorized as low, with the highest index value at station 1 at 0.766 and the lowest at station 2 by 0.66. Biavalvia distribution patterns in the region are random in species Anomalodiscus squamosus, Pitar citrus, Chamelea gillina, Mactra grandis, Hiatula chinensis, Tellina timorensis, Anadara granosa and are clustered in Placamen chlorotica species.